Sarcopenia is a risk factor for postoperative delirium in geriatric hip fracture patients: a retrospective study - Qi, Yi-Ming; Li, Hao-Tao; Chang, Shi-Min; Hu, Sun-Jun; Du, Shou-Chao; Liu, Chen-Dong; Chu, Yong-Qian; Rui, Yun-Feng (Frontiers in Medicine, 2025)
BackgroundVarious factors contribute to postoperative delirium (POD) in elderly patients undergoing hip fracture surgeries. Sarcopenia was defined as the progressive loss of skeletal muscle mass and strength associated with aging. The aim of this study was to explore the prevalence of POD and sarcopenia in geriatric patients undergoing hip fracture surgeries and to investigate the correlation between preoperative sarcopenia and POD.MethodsAfter applying specific inclusion and exclusion criteria, the information of 234 patients were retrospectively collected. POD was screened for with 4A’s Test and diagnosed with DSM-5 criteria. The incidences of POD and sarcopenia were calculated. The demographic and perioperative features as well as comorbidities of delirious and non-delirious patients were analyzed and the risk factors analysis for POD in elderly hip fracture patients were conducted through univariate analysis and multivariate regression analysis.Results48.7% patients were diagnosed of POD, 78.95% of which were females. The average age of delirious and non-delirious patients were 84.75 years and 80.63 years, respectively. The incidence of sarcopenia was 41.02% for all the included patients with 60.53% for delirious patients and 20.55% for non-delirious patients. Results of univariate analysis showed that sarcopenia (OR:5.281, 95%CI 2.988–9.337, p = 0.000), age increase per year (OR:1.128, 95CI 1.070–1.190, p = 0.000), operation duration increase (OR:1.017, 95%CI 1.004–1.030, p = 0.011), intertrochanteric fracture (OR:2.571, 95%CI 1.517–4.358, p = 0.000), dementia (OR: 6.029, 95%CI 2.532–14.359, p = 0.000), ASA > 2 (OR: 6.955, 95%CI 3.461–13.976, p = 0.000), coronary heart disease (OR: 2.201, 95%CI 1.257–3.854, p = 0.006), renal insufficiency (OR: 2.215, 95%CI 1.187–4.133, p = 0.012) and COPD (OR: 2.554, 95%CI 1.414–4.615, p = 0.002) were risk factors for POD. Results of multivariate analysis identified sarcopenia (OR: 2.457, 95% CI 1.226–4.923, p = 0.011), ASA > 2 (OR: 3.968, 95% CI 1.805–8.722, p = 0.001), dementia (OR: 3.912, 95% CI 1.390–11.014, p = 0.010) and coronary heart disease (OR: 2.176, 95% CI 1.044–4.538, p = 0.038) as independent risk factors for POD in geriatric hip fracture patients.ConclusionThe incidences of POD and sarcopenia in geriatric hip fracture patients are high. Sarcopenia is an independent risk factor for POD in geriatric hip fracture patients.